STRATEGI GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI 147 PALEMBANG - Nasution, Syamsiyah (IAIN Padangsidimpuan, 2019)
The purpose of research To determine student interest in the subject of Islamic education and strategies of teachers in the learning process to increase student interest in the subject of Islamic Education in SDN 147 Palembang. The research is a qualitative research, a study that aimed to describe and mengalisis phenomena and events .Teknik data collection through interviews, observation, questionnaire and documentation. The data used in this study are primary data and secondary data. Primary data is data obtained by researchers from the observation of the PAI teacher in the learning process in the classroom; to observe what strategies the teacher in the learning process, then the results of interviews with PAI teachers and principals; to determine student interest in the subject of PAI and development strategies for the improvement of teacher student interest in the subject of PAI, and the results of questionnaire to students; to gather data on student interest in the subject of PAI and strategies of teachers in thelearning process to increase studentinterest in the subject of PAI, while secondary data is data documentation consisting of the organizational structure, the profile of the school, teachers and state employees, the state of the student, and state-owned infrastructure sekolah.Adapun data management techniques through four stages namely; collecting data, classifying the data, explain the data, and draw conclusions. Based on the analysis of data it can be seen that, 1) Interest in learning fifth grade students on subjects PAI quite good. This is due to two factors that have supported the interests of learning, which is of concern and insentif.hal factor is evident from the presence in class, active involvement in the learning process, and compliance with the assignment of teachers either memorized or written. 2) Development of learning strategies used by teachers to increase student interest in the subject of Islamic Education in class V Elementary School 147 Palembang is good enough, it can be seen from the strategy gives attention of 80.90%, while the strategy is being or incentivize category enough is equal to 76.19%.